Detection of Clostridium difficile toxins by enzyme immunoassay. - Krishnan, C. (Cambridge University Press, 1986)
An enzyme-linked immunosorbent assay (ELISA) for the rapid diagnosis of antibiotic-associated colitis (AAC) is presented. Commercially available antisera to Clostridium difficile toxins contain antibodies to other antigens found in non-toxigenic C. difficile and other bacteria. Removal of these unwanted antibodies by absorption increased the specificity of ELISA for detection of C. difficile toxins. Specimens tested included 40 faecal extracts positive for cytotoxicity from cases of AAC, 30 diarrhoeic and 30 well-formed stools negative for cytotoxicity and 50 culture filtrates of toxigenic and non-toxigenic C. difficile and other clostridial species. Use of absorbed sera reduced false-positive reactions observed with faecal specimens from 23 to 8%. About 90% of specimens that were positive by the tissue culture cytotoxicity test were positive by ELISA using the absorbed sera. The relative merits of ELISA and other methods for the rapid diagnosis of AAC are discussed.